Strain induced structural phase transition and compositional dependent magnetic phase transition in Ti doped Bi0.80Ba0.20FeO3 ceramics. Issue 12 (December 2022) - Rana, Shohel; Karimunnesa, Syeda; Alam, F.; Chandra Das, Bablu; Khan, F.A.
Abstract: Bi0.80 Ba0.20 Fe1-x Tix O3 ( 0 ≤ x ≤ 0.10 ) samples are prepared using solid state reaction technique. Bi 3+ site is replaced with 20 % Ba 2+ which induced structural modification from rhombohedral to pseudo cubic accompanied by the creation of oxygen vacancies owing to the charge reimbursement. Fe 3+ site is replaced with different concentrations of Ti 4+ keeping Ba content fixed. All the samples exhibited similar morphology and no significant variation in grain size is observed by substituting Ti at Fe site. All of the samples exhibited ferromagnetic behavior, which is ascribed to the destruction of spiral spin structures and changes in super-exchange interaction strength caused by variations in bond lengths of Fe–O and Fe–O–Fe. The decrease in magnetization with increasing Ti concentration is due to magnetic moment dilution caused by non-magnetic Ti 4+ . An anomalous trend in magnetization is observed for magnetic measurements at low temperature (77 K) where structural transformation from ferromagnetic to diamagnetic behavior was noted for 10% Ti content. Further, because of the incorporation of Ti 4+, an improved dielectric property was observed due to increase in resistivity and decrease in the defect concentration (oxygen vacancies). In the present study, it was concluded that optimum concentration of Ba 2+ (20%) and Ti 4+ co-doped BiFeO3 systems have shown enhanced multiferroic properties at room temperature. Abstract : Rietveld refinement; Rhombohedral; Morphology; Ferromagnetic; Dielectric properties; Multiferroic properties.